Firm-specific training: Consequences for job mobility - Josef Zweimüller; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2000)
This paper analyzes the impact of formal training on worker mobility. Using data from the Swiss Labor Force Survey, we find that on-the-job search activities and, to a smaller extent, actual job separations are significantly affected by both employer-provided and general training. Moreover, while the separation probability of searching workers is strongly affected by previous firm-provided training, no such effect shows up for non-searchers. This is consistent with the hypothesis that workers bear most of the cost of specific training.
Keywords: J63; J24; 330; firm-specific training; on-the-job-search; turnover.; Betriebliches Bildungsmanagement; Arbeitsmobilität; Schweiz